Large energetic adaptations of elderly muscle to resistance and endurance training. - Jubrias SA; Esselman PC; Price LB; Cress ME; Conley KE (Journal of applied physiology (Bethesda, Md. : 1985), 2001)
This study determined the cellular energetic and structural adaptations of elderly muscle to exercise training. Forty male and female subjects (69.2 +/- 0.6 yr) were assigned to a control group or 6 mo of endurance (ET) or resistance training (RT). We used magnetic resonance spectroscopy and imaging to characterize energetic properties and size of the quadriceps femoris muscle. The phosphocreatine and pH changes during exercise yielded the muscle oxidative properties, glycolytic ATP synthesis, and contractile ATP demand. Muscle biopsies taken from the same site as the magnetic resonance measurements were used to determine myosin heavy chain isoforms, metabolite concentrations, and mitochondrial volume densities. The ET group showed changes in all energetic pathways: oxidative capacity (+31%), contractile ATP demand (-21%), and glycolytic ATP supply (-56%). The RT group had a large increase in oxidative capacity (57%). Only the RT group exhibited change in structural properties: a rise in mitochondrial volume density (31%) and muscle size (10%). These results demonstrate large energetic, but smaller structural, adaptations by elderly muscle with exercise training. The rise in oxidative properties with both ET and RT suggests that the aerobic pathway is particularly sensitive to exercise training in elderly muscle. Thus elderly muscle remains adaptable to chronic exercise, with large energetic changes accompanying both ET and RT.